Firefighters and Flame Retardant Activism. (February 2015) - Cordner, Alissa; Rodgers, Kathryn M.; Brown, Phil; Morello-Frosch, Rachel
In the past decade, exposure to flame retardant chemicals has become a pressing health concern and widely discussed topic of public safety for firefighters in the United States. Working through local, state, and national unions and independent health and advocacy organizations, firefighters have made important contributions to efforts to restrict the use of certain flame retardants. Firefighters are key members in advocacy coalitions dedicated to developing new environmental health regulations and reforming flammability standards to reflect the best available fire science. Their involvement has been motivated by substantiated health concerns and critiques of deceptive lobbying practices by the chemical industry. Drawing on observations and interviews with firefighters, fire safety experts, and other involved stakeholders, this article describes why firefighters are increasingly concerned about their exposure to flame retardant chemicals in consumer products, and analyzes their involvement in state and national environmental health coalitions.